A systematic review of randomized controlled clinical trials on the effectiveness of conservative management and physical therapy modalities in pregnancy-related back and pelvic girdle pain - Sima Raoofi; Vahideh Toopchizadeh; Soraya Babaie; Sanam Dolati; Kimia Motlagh; Parviz Saleh; Neda Dolatkhah (Mashhad University of Medical Sciences, 2023)
Introduction: Pregnancy-related back pain is one of the most common musculoskeletal disorders during pregnancy. In some women, pregnancy-related back pain can be the beginning of chronic back pain for the rest of life and the cause of subsequent problems and disabilities. This study was performed with aim to systematically review the effectiveness of conservative management and physical therapy modalities in pregnancy-related low back pain and pelvic girdle pain. Methods: A search was done in Persian language databases, including the Scientific Information Database (SID), MagIran, Iran Medex and the English-language EMBASE, including Web of Science, ClinicalTrials.gov, Scopus, Physiotherapy Evidence Database (PEDro), Allied and Complementary Medicine Database (AMED) and MEDLINE (Pubmed) without time limitation until September 2022 using the keywords included ("Pregnancy" OR "Postnatal Care") AND ("Pelvic Girdle Pain" OR "low back pain" OR "Lower Back Pain" OR "Low Back Ache") AND ("Conservative Management" OR "Self-management" OR "Complementary Medicine" OR "Alternative Medicine" OR "Alternative Therapy" OR "Physical Therapy" OR "Kinesio Tape" OR "Acupuncture" OR "Manual Therapy" OR "Muscle Training" OR "Cupping Treatment" OR "Cupping Therapy" OR "Cupping Treatment" OR "Acupressure" OR "Massage Therapy" OR "Belt" OR "Physical Activity" OR "Aquatic Therapy" OR "Hydrotherapy" OR "Exercise Therapy" ). The Cochrane Risk of Bias tool was applied to evaluate the quality of the studies. Results: Eighty-six articles entered the final results. Ergonomic training and low and moderate-intensity exercises lead to pain relief and functional improvement in pregnancy-related back or pelvic girdle pain sufferers. Local and auricular acupuncture, Kinesio taping, and modified belts separately or in combination with other methods lead to pain relief and improved performance. Conclusion: Clinicians can recommend conservative multidisciplinary management combining ergonomic training and exercise with acupuncture, Kinesio taping, and belts to manage pregnancy-related back and pelvic girdle pain. Care should be taken in choosing other interventions due to the lack of evidence.